Transformasi Sastra Sunda Modern pada Abad ke-19 sampai 20 M - Priska Marsila (Historia Madania: Jurnal Ilmu Sejarah, 2019)
Literature in Sundanese culture is constantly changing. At the end of the 19th century, Sundanese literature began to experience changes in the modern direction. This is likely due to the spread of the influence of translated European prose works. In this paper discusses how the transformation of Sundanese literature from traditional forms into modern literary forms. In addition, it also discusses the comparative analysis of literature contained in Wawacan Panji Wulung and the novel Baruang Ka Nu Ngarora. The method used in this study is to use the method of historical research supported by other disciplines, especially literature. Keywords: literature, wawacan, Sundanese novels.